Meningkatkan Hasil Belajar Pendidikan Pancasila Menggunakan Model Pembelajaran Cooperative Learning Tipe Teams Games Tournament - Sari, Nindi Novita (Jurnal Simki Postgraduate, 2025)
This classroom action research is motivated by the inaccuracy of the model teacher in choosing a learning model, which causes boredom and lack of focus for students in following the learning process. This study aims to determine the effect of the Cooperative learning model Teams Games Tournaments (TGT) type in improving the learning outcomes of fifth grade students in Pancasila education learning. The level of student focus in learning is still low, which results in low student learning outcomes, this is based on the results of observations that researchers have carried out. There are still many passive students. Therefore, researchers use the TGT type cooperative learning model to improve student learning outcomes. This study uses classroom action research. The subjects of this study were 20 fifth grade students of Bandar Lor 3 Public Elementary School. As the object of research are observation, documentation, and test methods. In conducting data analysis, this study uses three components of activities, namely data reduction, data presentation and conclusion drawing. Based on the research results, there was an improvement in student learning outcomes, as evidenced by the achievement of test scores. In Cycle II, the results of Pancasila education learning using the TGT cooperative learning model were considered complete. This improvement in student learning was further evident in the test results in Cycle II. Four students scored below the "not yet complete" level, while 16 completed the test, representing a percentage of 80%. This score exceeded the completion score by more than 70%. Therefore, during the final test of Cycle II, students achieved the minimum completion criteria (KKM) for the learning outcome test.